Rituals on Archaeological Site in Leran, Gresik, Indonesia - Irfanuddin Wahid Marzuki (Pascasarjana ISBI Bandung Conference Series, 2025)
Leran village has archaeological remains (tombs, menhir, stone mortar, dakon stones, mosques) that are scattered in several places. One of them is the oldest Islamic tomb in Indonesia, namely Fatimah binti Maemun 1802 A.D. These relics are until now visited by many people to hold religious rituals. This paper examines fundamental changes in pilgrimage ritual patterns, pilgrim activities and variable meanings established in religious rituals at archaeological sites. The method used in this study is qualitative descriptive research with a case study approach. The results showed changes in the implementation of religious rituals at archaeological sites in Leran that influenced the community's view of the existence of these archaeological sites. Keywords: ritual; archaeological site; pilgrimage